Garment Pleats Modeling and Force Analysis Based on Different Yarn Directions (Journal of Fiber Bioengineering and Informatics, 2021)
Pleating is a common modeling technique in the manufacturing of garments. As requirements for the style of pleats are gradually increasing, it is necessary to consider the pleats modeling and force conditions In this paper, draping experiments were carried out with the warp yarn on horizontal, vertical, and a 45\u25e6\u00a0angle (bias) for three types, After analyzing the modeling garment pleats, force conditions and comparing the angle of the resultant force, it can be concluded that the modeling and the force of the pleats varies with the direction of the yarn. The species of pleats are different and their modeling is forced differently. The results demonstrate that the modeling of draped pleats and sunray pleats-upper-length are mainly affected by gravity, the bias fabric was desirable in terms of roundness, symmetry and softness. For sunray pleats-whole-length style, the neckline, modeling, quantity and size of pleats, the stability of hem, and the effect of force should be rationally utilized to achieve the optimal styling. The modeling of mummy pleats was greatly affected by the stretch, the bias stripes were the optimal choice.